1994
DOI: 10.1161/01.atv.14.8.1315
|View full text |Cite
|
Sign up to set email alerts
|

Identification of matrix metalloproteinases 3 (stromelysin-1) and 9 (gelatinase B) in abdominal aortic aneurysm.

Abstract: A prominent metalloproteinase activity with an apparent molecular mass of 80 kD and additional activities at 67 through 70, 50, and 32 kD have been observed on casein, gelatin, and elastin gel zymography in extracts from abdominal aortic aneurysms (AAAs). The forms at 80, 50, and 32 kD were isolated by affinity to recombinant tissue inhibitor of metalloproteinases, and the 80-kD and 50-kD components were shown to be derived from matrix metalloproteinase-9 (MMP-9). The relative electrophoretic mobility of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(103 citation statements)
references
References 33 publications
(16 reference statements)
5
95
0
2
Order By: Relevance
“…[31][32][33] The dissolution of elastic fibers requires the presence of specific proteinases, and several elastolytic MMPs such as MMP-2, MMP-9, MMP-12 and MT1-MMP are thought to contribute to aneurysm development. 16,17,27,[34][35][36][37][38][39][40][41] MMP-9 has attracted particular interest, because it is the most abundant elastolytic proteinase secreted by human AAA tissue explants in vitro and is actively expressed by aneurysm-infiltrating macrophages located at the site of tissue damage in situ. Gene therapy for aortic aneurysm K Miwa et al MMP-9 expression also correlates with increasing aneurysm diameter, 18,43 and is elevated in the circulating plasma of patients with AAA.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] The dissolution of elastic fibers requires the presence of specific proteinases, and several elastolytic MMPs such as MMP-2, MMP-9, MMP-12 and MT1-MMP are thought to contribute to aneurysm development. 16,17,27,[34][35][36][37][38][39][40][41] MMP-9 has attracted particular interest, because it is the most abundant elastolytic proteinase secreted by human AAA tissue explants in vitro and is actively expressed by aneurysm-infiltrating macrophages located at the site of tissue damage in situ. Gene therapy for aortic aneurysm K Miwa et al MMP-9 expression also correlates with increasing aneurysm diameter, 18,43 and is elevated in the circulating plasma of patients with AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the extremely long half-life of elastin (Ϸ50 years), loss of elastin in adults almost certainly results from increased elastolysis rather than insufficient synthesis. 7,41 Nevertheless, elastogenesis in atherosclerosis may also be defective, producing poorly cross-linked immature elastin. 42,43 Elastic fibers can degenerate and alter their structure through aging; 44 elastolysis could also expose neoantigens that might provoke an autoimmune response.…”
Section: Collagenases and Elastases Associate With Aortic Aneurysm Dementioning
confidence: 99%
“…Since Busuttil, et al first reported that the AAA was associated with increased production of proteinases, 3) a variety of research has been performed to ascertain the increased expression of MMPs in AAAs. [4][5][6] Further, since the development of cDNA microarray methods, several studies have been performed to compare gene expression profiles of aneurysm specimens with those of normal aorta specimens, demonstrating many genes in aortic aneurysms were altered. [7][8][9] However, most of these reports compared aortic aneurysms with normal aorta obtained from non-age-matched cadavers, organ-transplant donors, or patients with aortoiliac occlusive diseases.…”
Section: Taketani Et Almentioning
confidence: 99%